The ferroptosis inducer RSL3 triggers interictal epileptiform activity in mice cortical neurons - Giustizieri, Michela; Petrillo, Sara; D’Amico, Jessica; Torda, Caterina; Quatrana, Andrea; Vigevano, Federico; Specchio, Nicola; Piemonte, Fiorella; Cherubini, Enrico (Frontiers in Cellular Neuroscience, 2023)
Epilepsy is a neurological disorder characterized by recurrent seizures, which result from excessive, synchronous discharges of neurons in different brain areas. In about 30% of cases, epileptic discharges, which vary in their etiology and symptomatology, are difficult to treat with conventional drugs. Ferroptosis is a newly defined iron-dependent programmed cell death, characterized by excessive accumulation of lipid peroxides and reactive oxygen species. Evidence has been provided that ferroptosis is involved in epilepsy, and in particular in those forms resistant to drugs. Here, whole cell patch clamp recordings, in current and voltage clamp configurations, were performed from layer IV principal neurons in cortical slices obtained from adult mouse brain. Application of the ferroptosis inducer RAS-selective lethal 3 (RSL3) induced interictal epileptiform discharges which started at RSL3 concentrations of 2 M and reached a plateau at 10 M. This effect was not due to changes in active or passive membrane properties of the cells, but relied on alterations in synaptic transmission. In particular, interictal discharges were dependent on the excessive excitatory drive to layer IV principal cells, as suggested by the increase in frequency and amplitude of spontaneously occurring excitatory glutamatergic currents, possibly dependent on the reduction of inhibitory GABAergic ones. This led to an excitatory/inhibitory unbalance in cortical circuits. Interictal bursts could be prevented or reduced in frequency by the lipophilic antioxidant Vitamin E (30 µM). This study allows identifying new targets of ferroptosis-mediated epileptic discharges opening new avenues for the treatment of drug-resistant forms of epilepsy.